Combining Consistency with Simplicity When Estimating Tax Incidence: Alternative Assumptions and Findings for Three Countries - Clive Bell; Christoph Rosenberg (Luxembourg Income Study (LIS), 1993)
Identifies, examines, and finds remedies for three forms of potential inconsistency that can arise in the Pechman-Musgrave method of estimating the distribution of the total tax burden using microdata sets. Several variants of shifting assumptions are formulated for analysis, in which the indexation of transfer incomes and the international mobility of capital play a central role. The resulting patterns of effective tax rates are quite sensitive not only to whether transfers are indexed, but also, in the case of the U.S., to whether capital is so mobile as to escape the burden of all taxes.
Keywords: 330